Reasonable suspicion in reporting child maltreatment: a survey among German healthcare professionals - Berthold, Oliver (Child Adolesc Psychiatry Ment Health, 2021)
BACKGROUND: With regular contacts to the general child population, healthcare professionals could play an important role in the detection of child maltreatment. However, a majority of child maltreatment cases go unnoticed by the healthcare system. Child protection legislations usually offer terms like “reasonable suspicion” to corner a threshold that warrants reporting to child protection services (CPS) is defined as. The indistinct legal terminology leads to marked differences in the interpretation of this threshold. Therefore, we aimed to systematically assess the understanding of reasonable suspicion and subsequent handling of cases in the German context. METHODS: A cross-sectional online survey was conducted among 2485 physicians and psychotherapists working with children and adolescents. Field access was gained by German professional associations. Via case vignettes, predictors of thresholds for reporting were assessed. RESULTS: The probability of a report to CPS increased positively with the degree of suspicion for maltreatment. However, even if participants were certain that child maltreatment occurred, 20% did not chose to report to CPS. Training in child protection lowered the professionals’ threshold for reasonable suspicion; experience with child protection cases and good knowledge of the legal framework increased the likelihood to report an alleged situation of child maltreatment to CPS. CONCLUSION: Our data show that a significant proportion of health care professionals are uncertain about estimating reasonable suspicion and on how to proceed when there are strong indications for child maltreatment Therefore, data point towards the relevance of training in child protection among healthcare professionals in order to improve detection and adequate handling of cases of child maltreatment. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s13034-021-00381-7.